PENINGKATAN HASIL BELAJAR IPA PADA TEMA PANAS DAN PERPINDAHANNYA MELALUI MODEL PEMBELAJARAN TAKE AND GIVE DI KELAS V SD NEGERI REUDEUP KABUPATEN ACEH BARAT - Yusransal Yusransal; Agustina Agustina; Mulya Arifah; Nurliana Nurliana; Anwar Kurniawan; Navi Ismail; Amiruddin Amiruddin; Teuku Salfiyadi (JGK (Jurnal Guru Kita), 2022)
Abstract: Improving Science Learning Outcomes on the Theme of Heat and Its Transfer through the Take And Give Learning Model in Class V Elementary School Reudeup, West Aceh Regency. The low learning outcomes are thought to be due to several factors, namely: (1) teacher-centered learning; (2) Students do not want to ask questions, let alone express opinions, (3) boredom and boredom of students in participating in science lessons; (4) Motivate students to be able to improve learning outcomes; (5) The application of the Take And Give learning model in the teaching and learning process to train students' creativity in the teaching and learning process. This study aims to determine the increase in science learning outcomes on the theme of heat and its transfer through the Take And Give learning model in the fifth grade of SD Negeri Reudeup, West Aceh Regency. The implementation of learning improvements in Classroom Action Research (CAR) was carried out at the Reudeup State Elementary School, Meureubo District, West Aceh Regency, which consisted of 3 stages of action, namely pre-action, cycle I and cycle II. The results showed that in the first cycle there were 14 students or 56% who completed with an average score of 66.4 while in the second cycle there were 21 students (84%) who completed with an average score of 76.4. Based on the results of the study, it can be concluded that the application of the take and give learning model in the heat theme and its transfer science subjects has a positive impact on the learning outcomes of fifth grade students at SD Negeri Reudeup. Keywords: Improvement, Learning Outcomes, Science, Take And Give Abstrak: Peningkatan Hasil Belajar Ipa Pada Tema Panas Dan Perpindahannya Melalui Model Pembelajaran Take And Give Di Kelas V Sd Negeri Reudeup Kabupaten Aceh Barat. Rendahnya hasil belajar diduga karena beberapa faktor yaitu : (1) pembelajaran yang masih berpusat pada guru (Teacher centered learning); (2)  Siswa tidak mau bertanya apalagi mengemukakan pendapat, (3) kejenuhan dan kebosanan siswa dalam mengikuti pelajaran IPA; (4) Memberi motivasi kepada siswa untuk dapat meningkatkan hasil belajar; (5) Penerapan model pembelajaran Take And Give dalam proses belajar mengajar untuk melatih kreatifitas siswa dalam proses belajar mengajar. Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar IPA pada tema panas dan perpindahannya melalui model pembelajaran Take And Give di kelas V SD Negeri Reudeup Kabupaten Aceh Barat. Pelaksanaan perbaikan pembelajaran dalam Penelitian Tindakan Kelas (PTK) ini dilaksanakan di Sekolah Dasar Negeri Reudeup Kecamatan Meureubo Kabupaten Aceh Barat, yang terdiri dari 3 tahap tindakan, yaitu pra tindakan, siklus I dan siklus II. Hasil penelitian menunjukkan pada siklus I ada 14 siswa atau 56% yang tuntas dengan nilai rata-rata 66,4 sedangkan pada siklus II ada 21 siswa (84%) yang tuntas dengan nilai rata-rata 76,4. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan model pembelajaran take and give pada mata pelajaran IPA tema panas dan perpindahannya berdampak positif terhadap hasil belajar siswa kelas V SD Negeri Reudeup. Kata Kunci : Peningkatan, Hasil Belajar, IPA, Take And Give